Answer:
30
Step-by-step explanation:
you divide 20 by 4 then multiply that by 6
Answer:
given
n=9
a=1
d=3-1=2
Step-by-step explanation:
now , by formula,
sn = n/2(2a+(n-1)d)
= 9/2(2×1+(9-1)×2)
=9/2×18
=81
Answer: 1.4 seconds
<u>Step-by-step explanation:</u>
The equation is: h(t) = at² + v₀t + h₀ where
- a is the acceleration (in this case it is gravity)
- v₀ is the initial velocity
- h₀ is the initial height
Given:
- a = -9.81 (if it wasn't given in your textbook, you can look it up)
- v₀ = 12
- h₀ = 3
Since we are trying to find out when it lands on the ground, h(t) = 0
EQUATION: 0 = 9.81t² + 12t + 3
Use the quadratic equation to find the x-intercepts
a=-9.81, b=12, c=3
![x=\dfrac{-b \pm \sqrt{b^2-4ac}}{2a}\\\\\\x=\dfrac{-(12)\pm \sqrt{(12)^2-4(-9.81)(3)}}{2(-9.81)}\\\\\\x=\dfrac{-12\pm 16.2}{-19.62}\\\\\\x=\dfrac{-12+ 16.2}{-19.62}=-0.2\qquad x=\dfrac{-12- 16.2}{-19.62}=\large\boxed{1.4}\\](https://tex.z-dn.net/?f=x%3D%5Cdfrac%7B-b%20%5Cpm%20%5Csqrt%7Bb%5E2-4ac%7D%7D%7B2a%7D%5C%5C%5C%5C%5C%5Cx%3D%5Cdfrac%7B-%2812%29%5Cpm%20%5Csqrt%7B%2812%29%5E2-4%28-9.81%29%283%29%7D%7D%7B2%28-9.81%29%7D%5C%5C%5C%5C%5C%5Cx%3D%5Cdfrac%7B-12%5Cpm%2016.2%7D%7B-19.62%7D%5C%5C%5C%5C%5C%5Cx%3D%5Cdfrac%7B-12%2B%2016.2%7D%7B-19.62%7D%3D-0.2%5Cqquad%20x%3D%5Cdfrac%7B-12-%2016.2%7D%7B-19.62%7D%3D%5Clarge%5Cboxed%7B1.4%7D%5C%5C)
Note: Negative time (-0.2) is not valid
4.0833 sorry if i’m wrong luv did you want it in a fraction?
The relationship between x and y is represent as:
Since, the relationship is linear.
The standard form of equation of line is:
![y-y_1=\frac{y_2-y_1}{x_2-x_1}(x-x_1)](https://tex.z-dn.net/?f=y-y_1%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%28x-x_1%29)
Consider any two set x and y values from the given relationship.
Let (-2, 10) and (-1,7.5)
![\text{Substitute x}_1=-2,y_1=10,x_2=-1,y_2=7.5\text{ in the standard equation of line.}](https://tex.z-dn.net/?f=%5Ctext%7BSubstitute%20x%7D_1%3D-2%2Cy_1%3D10%2Cx_2%3D-1%2Cy_2%3D7.5%5Ctext%7B%20in%20the%20standard%20equation%20of%20line.%7D)
![\begin{gathered} y-y_1=\frac{y_2-y_1}{x_2-x_1}(x-x_1) \\ y-10=\frac{7.5-10}{-1-(-2)}(x-(-2)) \\ y-10=\frac{-2.5}{1}(x+2) \\ y-10=-2.5(x+2) \\ y=-2.5(x+2)+10 \end{gathered}](https://tex.z-dn.net/?f=%5Cbegin%7Bgathered%7D%20y-y_1%3D%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D%28x-x_1%29%20%5C%5C%20y-10%3D%5Cfrac%7B7.5-10%7D%7B-1-%28-2%29%7D%28x-%28-2%29%29%20%5C%5C%20y-10%3D%5Cfrac%7B-2.5%7D%7B1%7D%28x%2B2%29%20%5C%5C%20y-10%3D-2.5%28x%2B2%29%20%5C%5C%20y%3D-2.5%28x%2B2%29%2B10%20%5Cend%7Bgathered%7D)
The equation of the linear relationship between x and y is:
y = -2.5(x + 2) + 10
Now, to check that the point (9, -17.5) lies on the represented relationship between x and y
Substitute x = 9 and y = -17.5 in the equation y = -2.5(x + 2) + 10
y = -2.5(x + 2) + 10
-17.5 = -2.5(9 + 2) + 10
-17.5 = -2.5(11) + 10
-17.5 = -27.5 + 10
-17.5 = -17.5
Thus, LHS = RHS
Hence the point (9, -17.5) lie on the given linear relationship between x and y.
Answer: The point (9, -17.5) lie on the given linear relationship between x and y.